Precision ADMET polyolefins containing dithiane: Synthesis, thermal properties, and macromolecular transformation. Issue 16 (8th April 2016) - Song, Shaofei; He, Feng; Fu, Zhisheng; Xu, Junting; Fan, Zhiqiang
ABSTRACT: 1, 3‐Dithiane and its derivatives are widely used as powerful acyl anion equivalent to a range of useful transformations that are needed in the synthesis of natural products. In this work, a series of polyolefins containing pendant dithiane groups have been designed and synthesized via acyclic diene metathesis polymerization (ADMET) polymerization and subsequent hydrogenation. The structures of these polymers were characterized by 1 H NMR, 13 C NMR, and FT‐IR, and successful incorporation of the dithiane groups was proved. With different contents of the dithiane moieties, these ADMET polymers exhibited distinct thermal properties different from each other as evidenced by differential scanning calorimetry and thermal gravimetric analysis. The dithiane units in the ADMET polymer with 20 methylene carbons between the adjacent dithiane groups were transformed into thiol groups via reaction with Bu3 SnH. This work provided a convenient route to synthesize polyethylene with pendant thiol groups that are evenly distributed in the chain. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2468–2475 Abstract : Three polyolefins containing pendant dithiane groups were synthesized via ADMET polymerization and subsequent hydrogenation. The polymer structures were characterized by 1 H NMR, 13 C NMR, and FT‐IR. These ADMET polymers exhibited distinct thermal properties different from each other as evidenced by DSC and TGA. Dithiane units in the polymer with 20 methylene carbons between the adjacent dithiane groups were transformed into thiol groups via reaction with Bu3 SnH. This work provided a convenient route to synthesize polyethylene with evenly distributed pendant thiol groups.